Discriminative ability of a nutritional risk questionnaire applied to patients with celiac disease - Viteri, Carmen; Arteaga, Cristina; Robayo, Verónica; Hidalgo, Kattyta; Guevara, Deysi (Data and Metadata, 2025)
A questionnaire can be a rapid tool to identify nutritional risk, allowing early intervention, especially in people with diseases such as celiac disease, where poor absorption of nutrients can cause severe deficiencies. This study assessed nutritional risk in 35 patients with prior informed consent, using a validated questionnaire, and analyzing its sensitivity and specificity. The study revealed that 65.7% are malnourished, with 48.6% underweight, especially children (72.7%) and adults (54.5%). In addition, 5.7% of patients, especially young people, are obese (16.7%). The application of the “Nutritional Screening Initiative” questionnaire showed that 66.7% are at nutritional risk, requiring improved eating habits. The correlation analysis indicated a significant association between BMI and nutritional risk. The ROC curve indicated a low discriminatory capacity, although the sensitivity was high (91.7%), correctly identifying cases at nutritional risk. However, at other thresholds, decision-making is almost random, as indicated by the sensitivity and specificity. It is concluded that the ROC curve suggested limitations in the capacity to discriminate nutritional risk, with a high sensitivity but moderate specificity. It is crucial to implement personalized nutritional interventions and improve classification models to more accurately identify risk in this population.